Quantitative and qualitative evaluation of the use of walls as a new perspective of rainwater harvesting - Marangoni, Thais Tonelli [UNESP]; Oliveira, Jefferson Nascimento de [UNESP]; Libanio, Marcelo (Assoc Brasileira Engenharia Sanitaria Ambiental, 2019)
The pollution of water supply sources and the need to seek water, which is increasingly distant, adds to the treated water a high monetary value, so the capture and use of rainwater represents a way to reduce costs. In large urban centers, the formation of heat islands takes place, which favors the occurrence of convective rains with winds. Furthermore, the buildings were verticalized, resulting in a larger lateral area compared to that of the roof, making the rainwater-harvesting in walls a promising alternative. The aim of this work was to verify the quantity and quality of the water collected on a glass wall and another concrete wall in the city of Ilha Solteira, Sao Paulo, Brazil. The average rainfall incidence was of 48.7% in the glass wall and of 33.3% in the concrete wall, with each screen having an average pickup efficiency of 16.21 and 827%, respectively. The parameters of water quality (pH, turbidity, electrical conductivity and alkalinity) presented a decrease with the passing of millimeters drained. Water from the glass wall requires no volume of waste according to NBR 15.527/07. No relation was found between rainfall intensity and water quality, as well as catchment efficiency. However, when rainfall occurred on consecutive days, the water quality was higher when compared to its occurrence in dry periods.
Keywords: rainwater; rainwater collection on walls; collecting surface; first-flush